Financial reporting of intangible assets in Islamic finance - Syed Musa Alhabshi; Hafiz Majdi Abdul Rashid; Sharifah Khadijah Syed Agil; Mezbah Uddin Ahmed (ISRA International Journal of Islamic Finance, 2017)
Purpose: This paper aims to address the financial reporting dimensions of intangible assets with specific reference to International Accounting Standards (IAS) 38 as well as relevant International Financial Reporting Standards (IAS 38 exclusion) that are embedded within intangible assets. These have implications for Islamic financial assets with identifiable and measurable intangible components. Design/methodology/approach The study uses the qualitative research method by way of interviews followed by focus group discussions with professional accountants/accounting academics and Sharīʿah scholars/advisors from academia, the industry and regulatory bodies. Analysis of relevant literature is made to understand the subject matter and Sharīʿah-related issues. Findings The study observes that the accounting dimensions of tangible assets are generally consistent with Sharīʿah requirements. However, significant variation arises when the dimensions of intangible assets are represented in financial assets. Research limitations/implications The paper presents an exploratory in-depth analysis within the context of intangible assets as specified in IAS 38. Originality/value The paper elucidates the comparative accounting dimensions and Sharīʿah requirements in reporting financial assets.
Keywords: 330; financial assets; Financial reporting; intangible assets; Islamic finance